Imaging studies of emission and laser scattering from a solution-cathode glow discharge. Issue 9 (21st May 2020) - Moon, Denise E.; Webb, Michael R.
Abstract : Imaging experiments were used to explore solution-to-plasma transport and plasma structure in a solution-cathode glow discharge. Abstract : Imaging experiments are performed on a solution-cathode glow discharge. Laser scattering is used to observe droplet trails ejected at a range of angles from the solution surface. Interference filters are used to photograph a variety of analyte emission lines and background emission bands. The effects of low molecular weight organic compounds (HCOOH and CH3 CH2 OH) and non-ionic surfactants (Triton X-45 and Triton X-405) on the spatial distributions of emission are studied. Low molecular weight organic compounds are found to affect the degree of emission for some species, but do not detectibly change the plasma structure. The lighter surfactant affects the degree of emission for some background species, but does not noticeably affect analyte emission or plasma structure. The heavier surfactant (Triton X-405) is found to affect both the degree of emission from some species and the overall structure of the plasma.